Pelatihan Pembuatan Produk Jajanan Sehat Berbahan Dasar Ikan sebagai Upaya Meningkatkan Keterampilan Ibu Rumah Tangga Di Desa Pantai Mekar, Kecamatan Muara Gembong, Bekasi - Mariani, Mariani; Artanti, Guspri Devi (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Pantai Mekar Village, which is located in Muara Gembong sub-district, Bekasi Regency, has a variety of superior local food ingredients, one of which is milkfish. However, the village community still did not have the awareness and skills to make milkfish as a material for healthy snacks products that have high selling value. This community service activity aims to increase the knowledge and skills of housewives in the village of Pantai Mekar in making healthy snack products made from fish. The method used in this community service activity is the provision of training and mentoring. The results of this community service activity showed an increase in the knowledge of the participants of the activity as measured by the results of the pre-test and post-test they did. Based on the results of the activity implementation questionnaire, 100% of the participants stated that they were motivated to become entrepreneurs and were interested in holding the next training.